Causes of violence among primary school students from the perspective of teachers - Nidham Abdul Jabbar Hussein; Karzan Mohammed Arif (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The purpose of this research is to determine the reasons for the violence among primary school students in the city of Sulaymaniyah and propose treatment or (solution) to them from the perspective of teachers for the year (2017-2018). The research sample consists of (176) teachers of the primary stage of both genders Where the choice was random in the research community. The research was conducted in (19) schools and (108) male teachers and (68) of female teachers. The researchers collected the necessary and important information for the research based on the form of the questionnaire and the previous researches, which included (5) different felds such as (media, social, psychological, familial, school) in (44) items. The researchers, after extracting the validity and reliability and preparing the device, they applied it to the real sample (teachers). Then after analyzing and canceling the questionnaire using the mean statistical equations and the percentage weight after the sequence of the axes, they presented the results of the research, saches: Media, especially television, neglecting students by their families and schools is of great importance in showing the phenomenon of violence among students. 2 - Punishment and the lack of understanding of families with the indifference of school administrators are considered the causes of the emergence of violence.